Designing A Knowledge Management-Based Framework For Operator Skill Transfer In Fast-Moving Consumer Goods (Fmcg) Manufacturing - Susilo Dwi Raharjo; Muhammad Yorga Permana (Publikasi Indonesia, 2026)
Background: PT XYZ, a biscuit manufacturer in Bekasi, West Java, faces a critical knowledge attrition risk as many senior operators in its wafer stick area approach retirement within five years, while new-operator onboarding is slow, changeover time is extended, and defect rates are higher. These symptoms point to a deeper issue: the critical knowledge for optimal operator performance is largely tacit and not yet documented in a transferable form.Objective: This research designs a structured Knowledge Management (KM) framework that addresses this risk through systematic operator skill-transfer mechanisms, guided by three research questions on current KM practice, the forms of critical knowledge required, and the aspired KM framework.Methods: A qualitative case study was conducted using semi-structured interviews with ten internal informants across four role levels and one external benchmark informant, supported by Gemba Walk observation and Work Instruction document review. Thematic analysis followed Braun and Clarke combined with the Gioia data-structure method, mapping 127 quotes to the five enablers of Milton and Lambe: Strategy, Governance, People, Process, and Technology.Results: Current KM practice is informal, individual-dependent, and reactive, with the most acute pain point being the broken Externalization mode of the SECI cycle. Troubleshooting emerges as the primary tacit competence differentiator and the largest documentation gap.Conclusion: The research proposes the KM House Framework for Operator Skill Transfer, positioning Strategy as the roof, Governance as the foundation, Process and People as the two pillars, Technology as the enveloping layer, and the SECI cycle as the engine, operationalized through a 12-month implementation roadmap.